Rehabilitation program for elderly to improve physical and cognitive activities using Nintendo Switch: A feasibility study in care settings - Andreia Maria Novo Lima; Maria Teresa Moreira; Maria Salomé Ferreira; Vítor Parola; Sandra Rodrigues; Ana Cristina Corucho Barbeitos Pinto; Telmo Lima Costa; Carla Sílvia Fernandes (Archives of Gerontology and Geriatrics Plus)
This study aimed to evaluate the usability of the Nintendo Switch for elderly individuals, including ease of use, understanding of the games, and the user interface, as well as to assess the engagement and adherence levels of elderly participants in the program. Over eight weeks, 14 elderly individuals participated in rehabilitation sessions using exergames, utilizing the Nintendo Switch twice a week. Usability was assessed through the System Usability Scale, and intrinsic motivation was measured using the Intrinsic Motivation Inventory. The participants, with an average age of 81.1 years, showed high inherent motivation (IMIp: 82.2 ± 9.9), but the usability of the Nintendo Switch was considered below average (SUS: 52.9 ± 14.1). Despite the high motivation, the usability of the Nintendo Switch was not ideal, although participants expressed enjoyment and interest in the activities. The need for prior training and integration on this technology, tailored to this age group and individually adjusted, is emphasized.